Clock component OsPRR73 positively regulates rice salt tolerance by modulating OsHKT2;1‐mediated sodium homeostasis. (21st December 2020) - Wei, Hua; Wang, Xiling; He, Yuqing; Xu, Hang; Wang, Lei
Abstract: The roles of clock components in salt stress tolerance remain incompletely characterized in rice. Here, we show that, among OsPRR ( Oryza sativa Pseudo‐Response Regulator ) family members, OsPRR73 specifically confers salt tolerance in rice. Notably, the grain size and yield of osprr73 null mutants were significantly decreased in the presence of salt stress, with accumulated higher level of reactive oxygen species and sodium ions. RNA sequencing and biochemical assays identified OsHKT2;1, encoding a plasma membrane‐localized Na + transporter, as a transcriptional target of OsPRR73 in mediating salt tolerance. Correspondingly, null mutants of OsHKT2;1 displayed an increased tolerance to salt stress. Immunoprecipitation‐mass spectrometry (IP‐MS) assays further identified HDAC10 as nuclear interactor of OsPRR73 and co‐repressor of OsHKT2;1 . Consistently, H3K9ac histone marks at OsHKT2;1 promoter regions were significantly reduced in osprr73 mutant. Together, our findings reveal that salt‐induced OsPRR73 expression confers salt tolerance by recruiting HDAC10 to transcriptionally repress OsHKT2;1, thus reducing cellular Na + accumulation. This exemplifies a new molecular link between clock components and salt stress tolerance in rice. SYNOPSIS: The circadian clock regulates abiotic stress tolerance in plants. Here, rice clock component OsPRR73 is shown to confer salt tolerance via chromatin modifications reducing sodium influx transporter OsHKT2;1 expression. OsPRR73 expression is transcriptionally induced by salt stress. osprr73 null mutants exhibit increased sensitivity to salt stress. OsPRR73 expression inhibits OsHKT2;1 transcription. OsPRR73 reduces histone H3K9 acetylation at the OsHKT2;1 promoter by recruiting histone deacetylase HDAC10. OsHKT2;1 loss enhances rice salt tolerance by reducing sodium ion and ROS accumulation. Abstract : A member of the pseudo response regulator (PRR) family in rice is induced upon salt stress to decrease expression of a sodium transporter via chromatin modifications.